Stock Market Reaction during the Global Financial Crisis in India: Fractal Analysis. (December 2014) - Mahalingam, Gayathri; Selvam, Murugesan
The Bombay Stock Exchange is the most popular and also the oldest stock exchange in Asia. It has the major number of listed companies in the world. In September 2008, the Sensex experienced huge falls, along with other markets around the world. Financial markets have become ever larger and financial crises have become more threatening to society. The devastating consequences of these crises stimulated the development of methods for predicting financial turmoil. New approaches to stock market prediction are considered on the basis of the intensity of stock index fluctuations estimated by fractal analysis techniques. Fractal analysis is used to analyse the financial time series. This article examined the fractal dimension in S&P BSE Sensex for pre- and post-recession periods—2004–2008 and 2008–2012 respectively.